Discovery of octopamine and tyramine in nectar and their effects on bumblebee behavior - Felicity Muth; Casey S. Philbin; Christopher S. Jeffrey; Anne S. Leonard (iScience, 2022)
Summary: Nectar chemistry can influence the behavior of pollinators in ways that affect pollen transfer, yet basic questions about how nectar chemical diversity impacts plant-pollinator relationships remain unexplored. For example, plants’ capacity to produce neurotransmitters and endocrine disruptors may offer a means to manipulate pollinator behavior. We surveyed 15 plant species and discovered that two insect neurotransmitters, octopamine and tyramine, were widely distributed in floral nectar. We detected the highest concentration of these chemicals in Citrus, alongside the well-studied alkaloid caffeine. We explored the separate and interactive effects of these chemicals on insect pollinators in a series of behavioral experiments on bumblebees (Bombus impatiens). We found that octopamine and tyramine interacted with caffeine to alter key aspects of bee behavior relevant to plant fitness (sucrose responsiveness, long-term memory, and floral preferences). These results provide evidence for a means by which synergistic or antagonistic nectar chemistry might influence pollinators.